Moral Peserta Didik dan Pendidikan Islam Menurut Pemikiran ‘Athiyah Al-Abrasyi - Fikri Abdul Aziz (Islamic University of Indonesia, 2020)
Basically, the real purpose of Islamic education is to produce moral students. The problem is that in Islamic Education there are still many moral deviations committed by people of various backgrounds and ages in Indonesia. Islamic education has not fully led to moral education. The purpose of this study was to determine the biography and thoughts of 'Athiyah al-Abrashyi in education, and the concept of moral education for students. This research method is library research. The results of this study indicate that the educational basis of 'Athiyah Al-Abrasyi brings the concept of a learning process that leads students to become adult humans. To achieve the true goal of Islamic education, 'Athiyah al-Abrashyi offers a concept of educational thought that can be used as a reference for education in Indonesia today.